2016
DOI: 10.12809/hkmj154803
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation for stroke prevention in elderly patients with non-valvular atrial fibrillation: what are the obstacles?

Abstract: options such as low-intensity warfarin and aspirin plus clopidogrel have been suggested but are inferior to dose-adjusted warfarin. Novel oral anticoagulants with promising efficacy and convenience hold great appeal. Optimal management of underlying medical conditions and modifiable stroke risk factors, together with intervention to improve the safe use of oral anticoagulants, are useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Among the reasons found in other series for the non-use of anticoagulant treatment were the risk of falls, history of hemorrhage, age, rejection of the family or patient, the presence of dementia and functional disability. 10,27 One in nine (11.6%) of the present patients treated with anticoagulants received a DOAC. These were mainly non-institutionalized patients in secondary prevention.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Among the reasons found in other series for the non-use of anticoagulant treatment were the risk of falls, history of hemorrhage, age, rejection of the family or patient, the presence of dementia and functional disability. 10,27 One in nine (11.6%) of the present patients treated with anticoagulants received a DOAC. These were mainly non-institutionalized patients in secondary prevention.…”
Section: Discussionmentioning
confidence: 85%
“…A younger age, the presence of heart failure or venous thromboembolism, higher functional capacity, higher BMI (as an indirect marker of lower sarcopenia), lower comorbidity (Charlson Comorbidity Index score) and a higher number of drugs were independently associated with anticoagulant treatment in the present population. Among the reasons found in other series for the non‐use of anticoagulant treatment were the risk of falls, history of hemorrhage, age, rejection of the family or patient, the presence of dementia and functional disability …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The lower risk of intracranial bleeding, as well as the practical advantages of NOACs over vitamin K antagonists (VKA), including a fixed dose, no need for International Normalized Ratio (INR) monitoring and fewer food and drug interactions, likely explain the observed increase in the proportion of patients receiving anticoagulant therapy. [1][2][3] Although this reduces the concern for "undertreatment" (ie, receiving no anticoagulant therapy at all), 4 new concerns have emerged about "underdosing" or off-label dose reduction: patients receiving an NOAC dose lower than recommended in the guidelines. 5,6 Previous studies reporting on the prevalence of off-label NOAC dose reduction have shown variable results, with estimates between 8% and 39%.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐vitamin K oral anticoagulants (NOACs, or direct acting oral anticoagulants, DOACs) play a central role in anticoagulant treatment for stroke prevention in patients with non‐valvular atrial fibrillation (AF). The lower risk of intracranial bleeding, as well as the practical advantages of NOACs over vitamin K antagonists (VKA), including a fixed dose, no need for International Normalized Ratio (INR) monitoring and fewer food and drug interactions, likely explain the observed increase in the proportion of patients receiving anticoagulant therapy 1–3 . Although this reduces the concern for “undertreatment” (ie, receiving no anticoagulant therapy at all), 4 new concerns have emerged about “underdosing” or off‐label dose reduction: patients receiving an NOAC dose lower than recommended in the guidelines 5,6 …”
Section: Introductionmentioning
confidence: 99%